PENGARUH PEMBERIAN EKSTRAK DAUN MIMBA (Azadirachta india A. Juss) TERHADAP HAMA KUTU DAUN (Aphis craccivora) PADA TANAMAN TERONG (Solanum melongena L) - Akhmad Syakur; Hasrianti; Muhammad Nur Alam; Budyanita Asrun (Jurnal Biogenerasi, 2022)
This study aims to determine the effect of neem leaf extract (Azadirachta indica A.Juss) against aphids (Aphis craccivora) on eggplant (Solanum melongena L) and to determine the concentration of neem leaf extract (Azadirachta indica A.Juss) which is effective in controlling the population aphids (Aphis craccivora) on eggplant (Solanum melongena L). This study used a randomized block design (RAK) consisting of 4 treatments and 3 replications. This treatment was based on the amount of concentration given to each group of eggplant (Solanum melongena L) consisting of P0 (Without treatment/Control), P1 (100 gr/1 liter of water), P2 (150 gr/1 liter of water), P3 (200 grams of water). gr/1 liter of water). The test results showed that neem leaf extract (Azadirachta indica A.Juss) treated with a concentration of 200 gr/1 liter of water was more effective in controlling the population of aphids (Aphis craccivora) on eggplant (Solanum melongena L) compared to other concentrations. The smallest concentration is 100 gr/1 liter of water. Neem leaf extract (Azadirachta indica A.Juss) was able to control the population of aphids because it has a high toxicity compound.